Environmental History in Croatian Historiography - Petrić, Hrvoje (Array, 2012)
Environmental history in Croatia has its origins in historical geography, although historians did not begin to take an interest in environmental topics specifically until the end of the 20th century. The article presents the development of environmental history in Croatian historiography.